K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 9 2015

1/ 3(x - 2) = 9 => x - 2 = 3 => x = 5

2/ 3(x - 36) = 216 => x - 36 = 72 => x = 108

3/ (x - 3)3 = 33 => x - 3 = 3 => x = 6

4/ 2x = 32 => 2x = 25 => x = 5

5/ 3x - 16 = 2.74 : 73 = 14 => 3x = 30 => x = 10

6/ (6x - 39) : 3 = 201 => 6x - 39 = 603 => 6x = 642 => x = 107

7/ (3x - 15)2 = 81 => (3x - 15)2 = 92 => 3x - 15 = 9 => 3x = 24 => x = 8

8/ 3(x + 4) = 105 => x + 4 = 35 => x = 31

9/ 12x - 43 = 4.84 : 83 = 32 => 12x = 32 : 64 => 12x = 1/2 => x = 1/24

10/ 41 - (2x - 5) = 680 => 2x - 5 = -639 => 2x = -634 => x = - 317

5 tháng 5 2018

a)

=> 2x2 = 98

=> x2 = 49

=> x = 7 

5 tháng 5 2018

\(a)2x^2-98=0\)               

   \(2x^2=0+98\)                

   \(2x^2=98\)                      

   \(x^2=98:2\)                

   \(x^2=49\)                 

\(\rightarrow x^2=7^2\)

\(\rightarrow x=7\)

Vậy x = 7

23 tháng 1 2019

a) x ( x + 0 ) = 0

x . x = 0

=> x =0

23 tháng 1 2019

b) ( x - 1 ) ( 7 - x ) = 0

=> x - 1 =0 hoặc 7 - x = 0

TH1 : x - 1 = 0

x = 0 + 1

x = 1

TH2 : 7 - x = 0

x = 7 - 0

x = 7

Vậy x = 1 hoặc x = 7

16 tháng 4 2020

a) \(\frac{3x}{-4}=\frac{-9}{6}\)

=> \(\frac{-3x}{4}=\frac{-9}{6}\)

=> \(\frac{-3x}{4}=\frac{-3}{2}\)

=> \(\frac{-3x}{4}=\frac{-6}{4}\)

=> \(-3x=-6\)

=> \(x=\left(-6\right):\left(-3\right)=2\)

b) \(\frac{2}{x}=\frac{y}{10}=\frac{4}{-5}\)

=> \(\frac{2}{x}=\frac{y}{10}=\frac{-4}{5}\)

+) \(\frac{2}{x}=\frac{-4}{5}\)

=> \(\left(-4\right)\cdot x=2\cdot5\)

=> \(\left(-4\right)\cdot x=10\)

=> \(x=\frac{10}{-4}=\frac{-10}{4}=\frac{-5}{2}\)

+) \(\frac{y}{10}=\frac{-4}{5}\)

=> \(5\cdot y=-40\)

=> \(y=\left(-40\right):5=-8\)

Vậy \(x=-\frac{5}{2},y=-8\)

c) \(\frac{7}{-x}=\frac{5}{y}=\frac{2}{34}\)

=> \(\frac{-7}{x}=\frac{5}{y}=\frac{1}{17}\)

+) \(\frac{-7}{x}=\frac{1}{17}\Rightarrow x=\left(-7\right)\cdot17=-119\)

+) \(\frac{5}{y}=\frac{1}{17}\Rightarrow y=5\cdot17=85\)

Vậy \(x=-119,y=85\)

d) \(\frac{x^2}{4}=16\)

=> \(x^2=16\cdot4=64\)

=> \(x\in\left\{8;-8\right\}\)

e) \(\frac{3}{x^3}=\frac{4}{-36}\)

=> \(\frac{3}{x^3}=\frac{1}{-9}=\frac{-1}{9}\)

=> \(x^3=3:\left(-\frac{1}{9}\right)=-27\)

=> \(x=-3\)

Vậy x = -3

\(a,1⋮\left(x+7\right)\)

\(\Rightarrow x+7\inƯ\left(1\right)=\left\{\pm1\right\}\)

Ta lập bảng xét giá trị 

x+71-1
x-6-8

\(b,4⋮x-5\)

\(x-5\inƯ\left(4\right)=\left\{\pm1;\pm2;\pm4\right\}\)

Ta lập bảng xét giá trị 

x-51-12-24-4
x6-47391
17 tháng 1 2020

a) -152 - (3x + 1) = (-2).(-3)3

-152 - 3x - 1 = (-2).(-27)

-3x - 153 = 54

-3x = 54 + 153

-3x = 207

x = -69

b) x - 43 = (35 - x) - 48

x - 43 = 35 - x - 48

x - 43= -x - 13

x = -x - 13 + 43

x = 30 + x

x + x = 30

2x = 30

x = 15

14 tháng 6 2016

1.(3x-1/4)^2=36

   (3x-1/4)^2=6^2

    3x-1/4    =6

    3x         =6+1/4

    3x         = 25/4

      x         =25/4:3

      x         =25/12

2.(1/4-2x)^3=8

   (1/4-2x)^3=2^3

     1/4-2x    =2

           2x    =1/4-2

           2x    =-7/4

             x    =-7/8 

3.(5-7/2x)^2=25

   (5-7/2x)^2=5^2

    5-7/2x     =5

       7/2x     =0

           x      =0

4.x+(1/4)^2=25

   x+1/16    =25

   x             =25-1/16

   x             =399/16

7.(2/5x-3/4)^2=1/9

   (2/5x-3/4)^2=(1/3)^2

    2/5x-3/4     =1/3

    2/5x           =1/3+3/4 

     2/5x           =13/12

         x            =13/12:2/5

         x            =65/24

8.(3/7-x)^2=1/49

   (3/7-x)^2=(1/7)^2

    3/7-x     =1/7

         x      =3/7-1/7

         x      =2/7

9.(2/3x+1/4)^3=125

   (2/3x+1/4)^3=5^3

    2/3x+1/4     =5

    2/3x            =5-1/4

    2/3x            =19/4

         x            =19/4:2/3

         x            =57/8 

10.(-3/4x+1/4)^2=25/16

     (-3/4x+1/4)^2=(5/4)^2

      -3/4x+1/4       =5/4 

      -3/4x              =5/4-1/4 

      -3/4x              =1

           x               =1:-3/4

           x               =-4/3

11.2.(x+1/4)^2=1/4

    2x^2+1/8    =1/4

     2x^2          =1/4-1/8

     2x^2          =1/8

       x^2          =1/8:2

       x^2          =1/16

       x             =1/4

    

15 tháng 6 2016

Còn câu 12 bạn ơi

15 tháng 7 2017

Ta có " (x - 5)7 = (x - 5)4

=> (x - 5)7 - (x - 5)= 0

<=> (x - 5)4[(x - 5)3 - 1] = 0

\(\Leftrightarrow\orbr{\begin{cases}\left(x-5\right)^4=0\\\left(x-5\right)^3-1=0\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\\left(x-5\right)^3=1\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\x-5=1\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x=5\\x=6\end{cases}}\)